A bottom-up lean implementation study at a Malaysian automotive parts manufacturer - Chay, Tick Fei (Cranfield University, 2014)
The aim of this research was to investigate shop floor employees’ involvement (including supervisory staffs) in lean implementation or Kaizen activities at a Malaysian automotive parts manufacturer leading in lean; and to propose a bottom-up lean conceptual model and its implementation roadmap to provoke involvement of shop floor employees in Kaizen. The research was carried out in five phases. First, the focus areas of Kaizen at Toyota and the critical success factors that would influence the extent of shop floor employees’ involvement in Kaizen activities were identified via literature review. Second, a case study was carried out at a Malaysian automotive parts manufacturer (known as Company A) with 7-years of intensive lean experience. The research data were collected via a semi-structured interview with the Lean Coordinator of the company, and a survey which addressed to different levels of internal stakeholder from top management to operators. Third, analyses on the extent of shop floor employees’ Kaizen involvement at Company A and the influences of each critical success factor were carried out. Fourth, a bottom-up lean conceptual model and its implementation roadmap incorporating the critical success factors were developed. Fifth, the proposed lean model and its implementation roadmap were validated by lean experts from both academia and industry. As a result, the study found the shop floor employees’ extent of involvement in Kaizen at Company A was low. The identified critical success factors namely F1 – top management’s commitment; F2 – shop floor employees’ commitment and technical capability; F3 – the stage of lean transformation; and F4 – shop floor responsibilities assignment were found to have significant influence on the extent of ‘Employee Involvement’. Being awarded as a Model Company in Malaysian automotive industry, Company A had yet to commence their transition to bottom-up approach phase in their lean journey although they had already enjoyed the early benefits of lean. The proposed model would thus serve as a general guideline to help the company or the Malaysian automotive industry in large in bottom-up approach lean implementation.
Keywords: lean production; lean thinking; Kaizen; employee involvement; bottom-up; framework; model; barrier; Malaysia; MAJAICO; SME; developing country